SOD1 misplacing and mitochondrial dysfunction in amyotrophic lateral sclerosis pathogenesis - Tafuri, Francesco; Ronchi, Dario; Magri, Francesca; Comi, Giacomo P.; Corti, Stefania (Frontiers in Cellular Neuroscience, 2015)
Amyotrophic Lateral Sclerosis (ALS) is a fatal motor neuron disease presenting as sporadic (sALS) or familial (fALS) forms. Even if the list of the genes underlining ALS greatly expanded, defects in SOD1, encoding the copper/zinc superoxide dismutase 1, still remain a major cause of fALS and are likely involved also in apparently sporadic presentations. The pathogenesis of ALS is still unknown, but several lines of evidence indicate that the mitochondrial accumulation of mutant SOD1 is an important mechanism of mitochondrial dysfunction, leading to motor neuron pathology and death. The intramitochondrial localization of mutant SOD1 is debated. Mutant SOD1 might accumulate inside the intermembrane space (IMS), overriding the physiological retention regulated by its chaperone CCS. On the other hand, misfolded SOD1 might deposit onto the outer mitochondrial membrane (OMM), clumping the transport across mitochondrial membranes and engaging mitochondrial-dependent cell apoptosis. The elucidation of the mechanisms ruling SOD1 localization and misplacing might shed light on peculiar ALS features such as cell selectivity and late onset. More importantly, these studies might disclose novel targets for therapeutic intervention in familial ALS as well as non-genetic forms. Finally, pharmacological or genetic manipulation aimed to prevent or counteract the intracellular shifting of mutant SOD1 could be effective for other neurodegenerative disorders featuring the toxic accumulation of misfolded proteins.